Efektifitas Senam Pilates terhadap Kualitas Tidur Ibu Hamil Trimester III - Rahmaini Fitri Harahap; Lisbeth Laora Silitonga (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Sleep quality is a measure where a person finds it easy to start sleeping, is able to maintain sleep quality and feels relaxed after waking from sleep. Sleep quality affects overall health and quality of life. The quality of a mother's sleep during pregnancy is heavily influenced by the physical and psychological changes she experiences. (Delaune & Ladner, 2011). Efforts that can be made to overcome sleep difficulties in pregnant women include doing light exercise that is safe for pregnant women, hypnotherapy, providing health education on how to maintain sleep quality and relaxation exercises. One of the sports that pregnant women can do is Pilates (Hegard, 2010). The purpose of this study is to identify and analyze the effectiveness of Pilates exercise on sleep quality in third trimester pregnant women. The research design used was a quasi-experimental, in the form of one group pre-test and post-test design. The sample in this study were pregnant women in the third trimester at Clinic Pratama Bunda Patimah as many 30 respondents. The sampling technique was carried out by consecutive sampling. Data collection techniques were carried out using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The PSQI is an effective instrument used to measure sleep quality and sleep patterns in adults. The results of the analysis using the bivariate Wilcoxon Signed Rank Test obtained a significance value of p value = 0.00 (p value <0.05). This means that there are differences in the quality of sleep of pregnant women before and after pilates exercise at Clinic Pratama Bunda Patimah, so that there is an influence of pilates exercise on the quality of sleep of pregnant women in the third trimester at Clinic Pratama Bunda Patimah. Keywords: Pilates Exercise, Sleep Quality, Pregnant Women, Third Trimester